The Differential Effect of Political Alliances on Trade by Regime Type: An Example from Korea - Kim, Yujin. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Economics.; Advisor: Enrico Spolaore.; Committee: Eoin Mcguirk.; Keywords: Economics, International relations, and Political science.